Tracking the Within‐Trial, Cross‐Trial, and Developmental Dynamics of Cognitive Control: Evidence From the Simon Task. Issue 6 (29th June 2018) - Erb, Christopher D.; Marcovitch, Stuart
Abstract : Six‐ to 8‐year‐olds, 10‐ to 12‐year‐olds, and adults ( N = 108) performed the Simon task by reaching to targets on a digital display. The spatial and temporal characteristics of their movements were used to assess how two key processes underlying cognitive control—a threshold adjustment process and a controlled selection process—unfold over the course of a response (within‐trial dynamics), are modulated by recent experience (cross‐trial dynamics), and contribute to age‐related gains in control (developmental dynamics). The results indicate that the controlled selection process undergoes a more protracted development than the threshold adjustment process. The results also shed light on a prominent debate concerning the cross‐trial dynamics of control by supporting the feature integration account over the conflict adaptation account.